Uneven ripening in 'Bangalore blue' grape (Vitis vinifera × Vitis labrusca) berries in India is linked to seed viability. Issue 2 (4th March 2017) - Shivashankar, Seshadri; Sumathi, Manoharan; Rao, Vala Keshava
ABSTRACT: Uneven ripening (UR) is a physiological disorder of unknown origin in 'Bangalore blue' grape ( Vitis vinifera × Vitis labrusca ) leading to wine of inferior quality. A preliminary study found wide variations in total dehydrogenase activity (TDH) of seeds from unevenly ripe berries. In our experiments, gibberellin (GA3 ) applied to young grapes increased seed TDH activity and reduced the incidence of uneven ripening to 2% compared with 35% in the control. In contrast, paclobutrazol (PBZ) decreased TDH activity and increased the incidence of the disorder to 58%. GA3 -treated berries had higher concentrations of sucrose and TDH activity in seed representing mature seeds with high viability. In contrast, PBZ-treated and control berries had higher concentrations of glucose and lower TDH activity, indicating immature seeds with low viability. These results suggested that competition among developing berries can lead to differences in seed gibberellin content, seed viability and the rate of berry growth resulting in green, purple, and black berries at harvest. The study established the role of seed viability in uneven ripening and demonstrated that the incidence of the disorder is reduced by the application of GA3 to immature berries.